Thermoplastic resin composition, molded article, and constituent member for IC socket for inspection
By thermoforming using a thermoplastic resin composition of a specific thermoplastic resin and an inorganic filler material, the problem of insufficient machining and fine machining of the molded body in the prior art is solved, and high-precision processing of IC socket components for inspection is achieved.
Patent Information
- Application Number
- CN202380048223.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-28
- Filing Date
- 2023-06-12
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art has shortcomings in the machining and fine machining properties of the molded body, especially when making the components of the IC socket for inspection, it is difficult to achieve high-precision machining.
A thermoplastic resin composition containing a specific thermoplastic resin and a specific inorganic filler material is used. Specifically, the component (A) is selected from the crystalline thermoplastic resin having a melting point of 270°C or higher and amorphous having a glass transition temperature of 200°C or higher. A thermoplastic resin, component (B): an inorganic filler containing zirconia. The composition is thermoformed to obtain excellent machining and fine machining.
It realizes molded bodies with excellent machining and fine machining properties, and is suitable for making components of IC sockets for inspection, etc., and improves processing accuracy and product quality.
Smart Images

Figure BDA0005197082490000031 
Figure BDA0005197082490000081 
Figure BDA0005197082490000082
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition, a molded product, and a component of an IC socket for inspection. Background Art
[0002] Engineering plastics are thermoplastic resins that have excellent properties such as moldability, heat resistance, and strength, and are used in a wide range of fields such as automotive parts, machine parts, and electrical / electronic parts.
[0003] It is also known that there are thermoplastic resin compositions containing functional fillers in engineering plastics. For example, Patent Document 1 describes that a low-pollution injection molded body is formed from a resin composition containing a thermoplastic resin component, a carbon precursor, and a conductive filler in predetermined amounts, wherein the thermoplastic resin component contains a crystalline thermoplastic resin and an amorphous thermoplastic resin, and the injection molded body can strictly control the surface resistivity to a desired value within the semi-conductive range, and the amount of foreign particles generated is significantly reduced.
[0004] Patent Document 2 discloses that a flame-retardant polyimide molding material contains a semi-aromatic polyimide resin and a predetermined amount of graphite, carbon fiber, etc., and has excellent molding processability and can exhibit high flame retardancy.
[0005] In addition, a test socket for checking the electrical characteristics of semiconductors / devices and testing whether they meet the desired specifications is known (see, for example, Patent Document 3). Patent Document 3 discloses that the ball guide film 180 constituting the test socket can be composed of a thin polyimide film with excellent wear resistance.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-290328
[0009] Patent Document 2: International Publication No. 2021 / 024624
[0010] Patent Document 3: Japanese Patent Application No. 2018-529932 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] According to records, the flame retardant polyimide molding material described in Patent Document 2 can also be applied to IC sockets for inspection. Examples of IC sockets for inspection include: IC sockets for product inspection (test sockets), IC sockets for aging tests (aging sockets), etc. There are many components that constitute these IC sockets for inspection. As components that can be applied to the flame retardant polyimide molding material, there can be cited a roughly flat component used in a location where a device to be inspected is installed. As a method for using a molded body containing a thermoplastic resin and an inorganic filler material such as the flame retardant polyimide molding material and manufacturing the aforementioned component, for example, there can be cited a method of cutting the aforementioned molded body to make a flat plate, and opening fine through holes on the flat plate to embed the aforementioned measuring device.
[0013] However, the prior art still has room for improvement in the machinability of the molded body and the micromachinability when the flat plate obtained by cutting is used to manufacture the components of the IC socket for inspection. For example, regarding the machinability of the molded body, when the molded body manufactured by injection molding is cut, if the surface of the obtained flat plate has large irregularities, it is not suitable for micromachining. In addition, regarding the micromachinability, when a plurality of through holes are opened at a narrow pitch on the obtained flat plate, if the pore size distribution increases, the pattern collapses, burrs, etc. occur, it is not suitable for manufacturing the components of the IC socket for inspection.
[0014] An object of the present invention is to provide a thermoplastic resin composition capable of producing a molded body having excellent machinability and micromachinability.
[0015] Solutions for solving problems
[0016] The present inventors have found that a thermoplastic resin composition containing a specific thermoplastic resin and a specific inorganic filler can solve the above-mentioned problems.
[0017] That is, the present invention relates to the following. [1]
[0019] A thermoplastic resin composition comprising a component (A) and a component (B),
[0020] Component (A): at least one thermoplastic resin selected from the group consisting of a crystalline thermoplastic resin (a1) having a melting point of 270° C. or higher and an amorphous thermoplastic resin (a2) having a glass transition temperature of 200° C. or higher,
[0021] Component (B): an inorganic filler material containing zirconium oxide (b1),
[0022] The content of the component (b1) is 2 to 40 parts by mass relative to 100 parts by mass of the component (A).
[0023] The content of the component (B) is 2 to 60 parts by mass relative to 100 parts by mass of the component (A). [2]
[0025] The thermoplastic resin composition according to the above [1], wherein the component (A) is at least one selected from the group consisting of polyimide resins, polyetherimide resins, polyetherimide sulfone resins, polyphenylene sulfide resins, polyetheretherketone resins, polyetherketoneketone resins, liquid crystal polymers, and wholly aromatic polyester resins other than liquid crystal polymers. [3]
[0027] The thermoplastic resin composition according to the above [1] or [2], wherein the above-mentioned component (A) comprises a polyimide resin (a1-1), wherein the polyimide resin (a1-1) comprises a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), and the content ratio of the repeating structural unit of the formula (1) is 20 to 70 mol% relative to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2).
[0028]
[0029] (R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms. X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.) [4]
[0031] The thermoplastic resin composition according to any one of [1] to [3] above, wherein the component (b1) has a volume median particle size (D50) of 1 μm or less. [5]
[0033] The thermoplastic resin composition according to any one of [1] to [4] above, wherein the component (b1) is a spherical particle. [6]
[0035] The thermoplastic resin composition according to any one of [1] to [5] above, wherein the component (B) further comprises an inorganic filler (b2) other than the component (b1), and the component (b2) is at least one selected from the group consisting of talc, mica, silica, alumina, silicon nitride, aluminum nitride, boron nitride, silicon carbide, boron carbide, calcium carbonate, and titanium oxide. [7]
[0037] The thermoplastic resin composition according to the above [6], wherein the content of the component (b2) is 1 to 40 parts by mass based on 100 parts by mass of the component (A). [8]
[0039] A molded article comprising the thermoplastic resin composition according to any one of [1] to [7] above. [9]
[0041] A component of an IC socket for inspection, which is obtained by processing the molded body described in [8] above.
[0042] Effects of the Invention
[0043] According to the thermoplastic resin composition of the present invention, a molded body having excellent machinability and micromachinability can be produced. The molded body is suitable for producing a component of an IC socket for inspection, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 1 is a schematic plan view showing one embodiment of a component 100 of a test IC socket. DETAILED DESCRIPTION
[0045] [definition]
[0046] In this specification, the molded body has excellent machinability, which means that when a molded body obtained by thermoforming a thermoplastic resin composition is subjected to cutting to produce a flat plate-shaped molded body (hereinafter also referred to as a "flat plate"), a flat plate with low surface roughness of the cut surface can be obtained. The surface roughness can be evaluated by the arithmetic mean roughness (Ra). It is further determined that when the warpage of the flat plate obtained by cutting is small, the molded body has more excellent machinability.
[0047] In this specification, the molded body has excellent micromachinability, which means that when a plurality of through holes are formed at a narrow pitch on the flat plate, the deviation of the hole diameter is small, pattern collapse, burrs, etc. are not likely to occur, and through holes with good appearance can be formed. The through holes mentioned here refer to fine through holes with a diameter of, for example, 200 μm or less, preferably 100 μm or less, and more preferably less than 100 μm, and the pitch is, for example, in the range of 1 to 5 times the diameter of the through holes.
[0048] The machinability and micromachinability can be specifically evaluated by the methods described in Examples.
[0049] [Thermoplastic resin composition]
[0050] The thermoplastic resin composition of the present invention contains a component (A) and a component (B), wherein the component (A) is at least one thermoplastic resin selected from the group consisting of a crystalline thermoplastic resin (a1) having a melting point of 270° C. or higher and an amorphous thermoplastic resin (a2) having a glass transition temperature of 200° C. or higher, and the component (B) is an inorganic filler containing zirconium oxide (b1), wherein the content of the component (b1) is 2 to 40 parts by mass relative to 100 parts by mass of the component (A), and the content of the component (B) is 2 to 60 parts by mass relative to 100 parts by mass of the component (A).
[0051] The thermoplastic resin composition of the present invention can produce a molded body having excellent machinability and micromachinability by using a thermoplastic resin (A) having predetermined thermal properties and a predetermined amount of an inorganic filler (B) containing zirconium oxide (b1). As described later, the volume median particle size (D50) of zirconium oxide (b1) is preferably 1 μm or less.
[0052] The reason why the present invention can achieve the above-mentioned effect is still uncertain, but it is speculated that by using submicron-level tiny zirconium oxide (b1) particles as inorganic fillers, the unevenness caused by particles existing on the cutting surface can be suppressed, and low surface roughness can be achieved. It is also believed that when the molded body is formed with fine through holes, the wall surface of the fine through holes is also kept smooth, so the accuracy of hole formation is improved, and the increase in pore size distribution and pattern collapse can be suppressed. It is also speculated that by containing a high-hardness component (b1) in a specified amount relative to the thermoplastic resin (A), the material is moderately brittle, and the generation of burrs can be suppressed.
[0053] <Thermoplastic resin (A)>
[0054] The thermoplastic resin (A) used in the present invention (hereinafter also referred to as "component (A)" or "thermoplastic resin (A)") is at least one selected from the group consisting of a crystalline thermoplastic resin (a1) having a melting point of 270°C or higher and an amorphous thermoplastic resin (a2) having a glass transition temperature of 200°C or higher.
[0055] In this specification, a crystalline thermoplastic resin refers to a resin having a melting point and a glass transition temperature, and an amorphous thermoplastic resin refers to a resin having a glass transition temperature but no melting point. It should be noted that resins that are essentially crystalline but have an extremely slow crystallization rate and can only be processed in an amorphous state in various molding methods are classified as amorphous thermoplastic resins.
[0056] (Crystalline thermoplastic resin (a1))
[0057] The crystalline thermoplastic resin (a1) (hereinafter also referred to as "component (a1)") used as the component (A) has a melting point of 270°C or higher from the viewpoint of producing a molded body having excellent machinability and micromachinability.
[0058] From the viewpoint of improving the machinability and micromachinability of the obtained molded body, the melting point of component (a1) is preferably 280° C. or higher, more preferably 290° C. or higher, and further preferably 300° C. or higher. From the viewpoint of ease of thermoforming, it is preferably 400° C. or lower, more preferably 380° C. or lower, and further preferably 350° C. or lower.
[0059] The melting point of the component (a1) can be measured using a differential scanning calorimeter apparatus and specifically by the method described in Examples.
[0060] The glass transition temperature (Tg) of component (a1) is not particularly limited. From the viewpoint of improving the machinability and micromachinability of the obtained molded body, it is preferably 130°C or more, more preferably 140°C or more, and further preferably 150°C or more. From the viewpoint of ease of molding, it is preferably 250°C or less, more preferably 230°C or less, and further preferably 200°C or less.
[0061] The glass transition temperature of the component (a1) can be measured using a differential scanning calorimeter apparatus and specifically by the method described in Examples.
[0062] (Amorphous thermoplastic resin (a2))
[0063] The amorphous thermoplastic resin (a2) (hereinafter also referred to as "component (a2)") used as component (A) is an amorphous thermoplastic resin having a glass transition temperature of 200°C or higher from the viewpoint of producing a molded body having excellent machinability and fine processing properties.
[0064] From the viewpoint of improving the machinability and micromachinability of the obtained molded body, the glass transition temperature (Tg) of component (a2) is preferably 210°C or higher, more preferably 230°C or higher, and further preferably 250°C or higher. From the viewpoint of ease of thermoforming, it is preferably 400°C or lower, more preferably 350°C or lower, and further preferably 300°C or lower.
[0065] The glass transition temperature of the component (a2) can be measured by the same method as described above.
[0066] Examples of component (A) include thermoplastic resins that are either component (a1) or component (a2) such as polyimide resins, polyamide resins, polyetherimide resins, polyetherimide sulfone resins, polyphenylene sulfide resins, polyetheretherketone resins, polyetherketoneketone resins, polycarbonate resins, polyamideimide resins, polysulfone resins, polyethersulfone resins, polyarylate resins, liquid crystal polymers, wholly aromatic polyester resins other than liquid crystal polymers, polyetherketone resins, polyetheretherketoneketone resins, and polybenzimidazole resins.
[0067] Among the above, from the viewpoint of producing a molded body with excellent machinability and micromachinability, component (A) is preferably at least one selected from the group consisting of polyimide resin, polyetherimide resin, polyetherimide sulfone resin, polyphenylene sulfide resin, polyetheretherketone resin, polyetherketoneketone resin, liquid crystal polymer, and wholly aromatic polyester resin other than liquid crystal polymer; more preferably at least one selected from the group consisting of polyimide resin, polyetherimide resin, polyphenylene sulfide resin, and polyetheretherketone resin. In the case of requiring low dielectric properties, component (A) is more preferably a polyimide resin, among which a polyimide resin having an aliphatic structure (other than wholly aromatic) and a polyimide resin having a bulky structure such as a halogen.
[0068] As component (A), component (a1), component (a2), or a mixture of component (a1) and component (a2) can be used. From the viewpoint of improving the machinability and micromachinability of the obtained molded body, component (A) preferably contains component (a1) which is a crystalline thermoplastic resin.
[0069] From the viewpoint of improving the machinability and fine processing properties of the obtained molded body, the content of component (a1) in component (A) is preferably 50 mass % or more, more preferably 60 mass % or more, further preferably 70 mass % or more, further preferably 80 mass % or more, further preferably 90 mass % or more, and is 100 mass % or less.
[0070] When component (A) includes component (a1), from the viewpoint of improving the machinability and micromachinability of the obtained molded body, the viewpoint of the ease of thermoforming, and the viewpoint of obtaining low dielectric properties, the component (a1) is more preferably a polyimide resin, and further preferably a polyimide resin (a1-1), wherein the polyimide resin (a1-1) includes a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), and the content ratio of the repeating structural unit of the formula (1) is 20 to 70 mol% relative to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2).
[0071]
[0072] (R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms. X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.)
[0073] The polyimide resin (a1-1) is a crystalline thermoplastic resin, and its form is preferably powder or pellets. For this polyimide resin, it is different from a polyimide resin having no glass transition temperature (Tg) formed by closing the imide ring after molding in the state of a polyimide precursor such as polyamic acid, or a polyimide resin that decomposes at a temperature below the glass transition temperature.
[0074] The repeating structural unit of formula (1) is described in detail below.
[0075] R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure. Here, the alicyclic hydrocarbon structure refers to a ring derived from an alicyclic hydrocarbon compound, and the alicyclic hydrocarbon compound may be saturated or unsaturated and may be monocyclic or polycyclic.
[0076] Examples of the alicyclic hydrocarbon structure include, but are not limited to, cycloalkane rings such as cyclohexane rings, cycloalkene rings such as cyclohexene, bicycloalkane rings such as norbornane rings, and bicycloalkene rings such as norbornene. Among these, cycloalkane rings are preferred, cycloalkane rings having 4 to 7 carbon atoms are more preferred, and cyclohexane rings are still more preferred.
[0077] The carbon number of R1 is 6-22, preferably 8-17.
[0078] R1 contains at least one alicyclic hydrocarbon structure, and preferably contains 1 to 3 alicyclic hydrocarbon structures.
[0079] R1 is preferably a divalent group represented by the following formula (R1-1) or (R1-2).
[0080]
[0081] (m 11 and m 12 Each independently represents an integer of 0 to 2, and is preferably 0 or 1. 13 ~m 15 Each independently represents an integer from 0 to 2, preferably 0 or 1.)
[0082] R1 is particularly preferably a divalent group represented by the following formula (R1-3).
[0083]
[0084] In addition, in the divalent group represented by the above formula (R1-3), the positional relationship of the two methylene groups with respect to the cyclohexane ring may be either cis or trans, and the ratio of cis to trans may be any value.
[0085] X1 is a tetravalent group having 6 to 22 carbon atoms and including at least one aromatic ring. The aromatic ring may be a monocyclic ring or a condensed ring, and examples thereof include, but are not limited to, a benzene ring, a naphthalene ring, an anthracene ring, and a tetracene ring. Among these, a benzene ring and a naphthalene ring are preferred, and a benzene ring is more preferred.
[0086] X1 has 6 to 22 carbon atoms, preferably 6 to 18 carbon atoms.
[0087] X1 contains at least one aromatic ring, preferably 1 to 3 aromatic rings.
[0088] X1 is preferably a tetravalent group represented by any of the following formulae (X-1) to (X-4).
[0089]
[0090] (R 11 ~R 18 Each is independently an alkyl group having 1 to 4 carbon atoms. 11 ~p 13 Each independently represents an integer of 0 to 2, and is preferably 0. 14 、p 15 、p 16 and p 18 Each independently represents an integer of 0 to 3, and is preferably 0. 17 is an integer of 0 to 4, preferably 0. 11 ~L 13 Each is independently a single bond, an ether group, a carbonyl group or an alkylene group having 1 to 4 carbon atoms.)
[0091] It should be noted that X1 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. Therefore, R in formula (X-2) is selected so that the number of carbon atoms in the tetravalent group represented by formula (X-2) falls within the range of 10 to 22. 12 , R 13 、p 12 and p 13 .
[0092] Similarly, L in formula (X-3) is selected so that the carbon number of the tetravalent group represented by formula (X-3) falls within the range of 12 to 22. 11 , R 14 , R 15 、p 14 and p 15L in formula (X-4) is selected so that the carbon number of the tetravalent group represented by formula (X-4) falls within the range of 18 to 22. 12 , L 13 , R 16 , R 17 , R 18 、p 16 、p 17 and p 18 .
[0093] X1 is particularly preferably a tetravalent group represented by the following formula (X-5) or (X-6).
[0094]
[0095] Next, the repeating structural unit of formula (2) is described in detail as follows.
[0096] R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms, preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and still more preferably 8 to 10 carbon atoms. Here, the chain aliphatic group refers to a group derived from a chain aliphatic compound, and the chain aliphatic compound may be saturated or unsaturated, may be straight chain or branched, and may contain heteroatoms such as oxygen atoms.
[0097] R2 is preferably an alkylene group having 5 to 16 carbon atoms, more preferably an alkylene group having 6 to 14 carbon atoms, and still more preferably an alkylene group having 7 to 12 carbon atoms, and among these, preferably an alkylene group having 8 to 10 carbon atoms. The alkylene group may be either a linear or branched chain, and is preferably a linear chain chain.
[0098] R2 is preferably at least one selected from the group consisting of an octamethylene group and a decamethylene group, and particularly preferably an octamethylene group.
[0099] In addition, other suitable embodiments of R2 include: a divalent chain aliphatic group having 5 to 16 carbon atoms including an ether group. The carbon number is preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and even more preferably 8 to 10 carbon atoms. Among them, a divalent group represented by the following formula (R2-1) or (R2-2) is preferred.
[0100] -(CH2) m21 -O-(CH2) m22 - -(CH2) m23 -O-(CH2) m24 -O-(CH2) m25 -
[0101] (R2-1) (R2-2)
[0102] (m 21 and m22 Each independently represents an integer of 1 to 15, preferably 1 to 13, more preferably 1 to 11, and even more preferably 1 to 9. 23 ~m 25 Each independently represents an integer of 1 to 14, preferably 1 to 12, more preferably 1 to 10, and even more preferably 1 to 8.)
[0103] It should be noted that R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms (preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and further preferably 8 to 10 carbon atoms). Therefore, m in the formula (R2-1) is selected so that the number of carbon atoms of the divalent group represented by the formula (R2-1) falls within the range of 5 to 16 (preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and further preferably 8 to 10 carbon atoms). 21 and m 22 That is, m 21 +m 22 It is 5 to 16 (preferably 6 to 14, more preferably 7 to 12, and even more preferably 8 to 10).
[0104] Similarly, m in formula (R2-2) is selected so that the carbon number of the divalent group represented by formula (R2-2) falls within the range of 5 to 16 (preferably 6 to 14 carbon numbers, more preferably 7 to 12 carbon numbers, and even more preferably 8 to 10 carbon numbers). 23 ~m 25 That is, m 23 +m 24 +m 25 The carbon number is 5 to 16 (preferably 6 to 14 carbon atoms, more preferably 7 to 12 carbon atoms, and even more preferably 8 to 10 carbon atoms).
[0105] The definition of X2 is the same as that of X1 in formula (1), and the preferred embodiments are also the same.
[0106] The content ratio of the repeating structural unit of formula (1) is 20 to 70 mol% relative to the sum of the repeating structural unit of formula (1) and the repeating structural unit of formula (2). When the content ratio of the repeating structural unit of formula (1) is within the above range, the polyimide resin (a1-1) can be fully crystallized even in a normal injection molding cycle. If the content ratio is less than 20 mol%, the thermoformability is reduced, and if it exceeds 70 mol%, the crystallinity is reduced, thereby reducing the heat resistance.
[0107] From the viewpoint of exhibiting high crystallinity, the content ratio of the repeating structural unit of formula (1) relative to the total of the repeating structural unit of formula (1) and the repeating structural unit of formula (2) is preferably 65 mol% or less, more preferably 60 mol% or less, and further preferably 50 mol% or less.
[0108] The content ratio of the repeating structural unit of formula (1) relative to the total of the repeating structural unit of formula (1) and the repeating structural unit of formula (2) is preferably 20 mol% or more and less than 40 mol%. When it is within this range, the crystallinity of the polyimide resin (a1-1) becomes higher, and a resin composition with better heat resistance can be obtained.
[0109] From the viewpoint of thermoformability, the content ratio is preferably 25 mol % or more, more preferably 30 mol % or more, and even more preferably 32 mol % or more, and from the viewpoint of expressing high crystallinity, it is even more preferably 35 mol % or less.
[0110] The total content ratio of the repeating structural units of the formula (1) and the repeating structural units of the formula (2) relative to all the repeating structural units constituting the polyimide resin (a1-1) is preferably 50 to 100 mol %, more preferably 75 to 100 mol %, further preferably 80 to 100 mol %, and further preferably 85 to 100 mol %.
[0111] The polyimide resin (a1-1) may also contain a repeating structural unit of the following formula (3). In this case, the repeating structural unit of formula (3) is preferably contained in an amount of 25 mol% or less relative to the sum of the repeating structural unit of formula (1) and the repeating structural unit of formula (2). On the other hand, the lower limit is not particularly limited, and may be more than 0 mol%.
[0112] From the viewpoint of improving heat resistance, the content ratio is preferably 5 mol % or more, more preferably 10 mol % or more, and from the viewpoint of maintaining crystallinity, it is preferably 20 mol % or less, more preferably 15 mol % or less.
[0113]
[0114] (R3 is a divalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. X3 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.)
[0115] R3 is a divalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. The aromatic ring may be a monocyclic ring or a condensed ring, and examples thereof include, but are not limited to, a benzene ring, a naphthalene ring, an anthracene ring, and a tetracene ring. Among these, a benzene ring and a naphthalene ring are preferred, and a benzene ring is more preferred.
[0116] The carbon number of R3 is 6-22, preferably 6-18.
[0117] R3 contains at least one aromatic ring, preferably 1 to 3 aromatic rings.
[0118] In addition, a monovalent or divalent electron-withdrawing group may be bonded to the aromatic ring. Examples of monovalent electron-withdrawing groups include nitro, cyano, p-toluenesulfonyl, halogen, alkyl halide, phenyl, acyl, and the like. Examples of divalent electron-withdrawing groups include fluorinated alkylene groups (e.g., -C(CF3)2-, -(CF2) p -(herein, p is an integer of 1 to 10))) In addition to the halogenated alkylene group, -CO-, -SO2-, -SO-, -CONH-, -COO- and the like can be mentioned.
[0119] R3 is preferably a divalent group represented by the following formula (R3-1) or (R3-2).
[0120]
[0121] (m 31 and m 32 Each independently represents an integer of 0 to 2, and is preferably 0 or 1. 33 and m 34 Each independently represents an integer of 0 to 2, and is preferably 0 or 1. 21 , R 22 and R 23 Each is independently an alkyl group having 1 to 4 carbon atoms, an alkenyl group having 2 to 4 carbon atoms, or an alkynyl group having 2 to 4 carbon atoms. 21 、p 22 and p 23 is an integer of 0 to 4, preferably 0. 21 is a single bond, an ether group, a carbonyl group, or an alkylene group having 1 to 4 carbon atoms.
[0122] It should be noted that R3 is a divalent group having 6 to 22 carbon atoms and containing at least one aromatic ring. Therefore, m in formula (R3-1) is selected so that the number of carbon atoms of the divalent group represented by formula (R3-1) falls within the range of 6 to 22. 31 、m 32 , R 21 and p 21 .
[0123] Similarly, L in the formula (R3-2) is selected so that the carbon number of the divalent group represented by the formula (R3-2) falls within the range of 12 to 22. 21 、m 33 、m 34 , R 22 , R 23 、p 22 and p 23 .
[0124] The definition of X3 is the same as that of X1 in formula (1), and the preferred embodiments are also the same.
[0125] The polyimide resin (a1-1) may further contain a repeating structural unit represented by the following formula (4).
[0126]
[0127] (R4 is -SO2- or -Si(R x )(R y )O- divalent group, R x and R y Each independently represents a chain aliphatic group having 1 to 3 carbon atoms or a phenyl group. X4 is a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.
[0128] The definition of X4 is the same as that of X1 in formula (1), and the preferred embodiments are also the same.
[0129] The terminal structure of the polyimide resin (a1-1) is not particularly limited, but it is preferred that the terminal has a chain aliphatic group having 5 to 14 carbon atoms.
[0130] The chain aliphatic group may be saturated or unsaturated, and may be linear or branched. When the polyimide resin (a1-1) has the above-mentioned specific group at the terminal, a resin composition having excellent heat aging resistance can be obtained.
[0131] Examples of the saturated chain aliphatic group having 5 to 14 carbon atoms include n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, lauryl, n-tridecyl, n-tetradecyl, isopentyl, neopentyl, 2-methylpentyl, 2-methylhexyl, 2-ethylpentyl, 3-ethylpentyl, isooctyl, 2-ethylhexyl, 3-ethylhexyl, isononyl, 2-ethyloctyl, isodecyl, isododecyl, isotridecyl, and isotetradecyl.
[0132] Examples of the unsaturated linear aliphatic group having 5 to 14 carbon atoms include 1-pentenyl, 2-pentenyl, 1-hexenyl, 2-hexenyl, 1-heptenyl, 2-heptenyl, 1-octenyl, 2-octenyl, nonenyl, decenyl, dodecenyl, tridecenyl and tetradecenyl.
[0133] Among them, the above-mentioned chain aliphatic group is preferably a saturated chain aliphatic group, and more preferably a saturated straight-chain aliphatic group. In addition, from the viewpoint of obtaining heat aging resistance, the above-mentioned chain aliphatic group is preferably a carbon number of 6 or more, more preferably a carbon number of 7 or more, and further preferably a carbon number of 8 or more, and preferably a carbon number of 12 or less, more preferably a carbon number of 10 or less, and further preferably a carbon number of 9 or less. The above-mentioned chain aliphatic group may be only one kind, or may be two or more kinds.
[0134] The above-mentioned chain aliphatic group is particularly preferably at least one selected from the group consisting of n-octyl, isooctyl, 2-ethylhexyl, n-nonyl, isononyl, n-decyl and isodecyl; further preferably at least one selected from the group consisting of n-octyl, isooctyl, 2-ethylhexyl, n-nonyl and isononyl; most preferably at least one selected from the group consisting of n-octyl, isooctyl and 2-ethylhexyl.
[0135] In addition, from the viewpoint of heat aging resistance, the polyimide resin (a1-1) preferably has only a linear aliphatic group having 5 to 14 carbon atoms at the terminal, except for a terminal amine group and a terminal carboxyl group. When a group other than the above is present at the terminal, the content thereof is preferably 10 mol% or less, more preferably 5 mol% or less, relative to the linear aliphatic group having 5 to 14 carbon atoms.
[0136] From the viewpoint of showing excellent heat aging resistance, the content of the above-mentioned chain aliphatic group with 5 to 14 carbon atoms in the polyimide resin (a1-1) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, and further preferably 0.2 mol% or more, relative to 100 mol% of the total of all repeating structural units constituting the polyimide resin (a1-1). In addition, in order to ensure sufficient molecular weight and obtain good mechanical properties, the content of the above-mentioned chain aliphatic group with 5 to 14 carbon atoms in the polyimide resin (a1-1) is preferably 10 mol% or less, more preferably 6 mol% or less, and further preferably 3.5 mol% or less, relative to 100 mol% of the total of all repeating structural units constituting the polyimide resin (a1-1).
[0137] The content of the linear aliphatic group having 5 to 14 carbon atoms in the polyimide resin (a1-1) can be determined by depolymerizing the polyimide resin (a1-1).
[0138] The polyimide resin (a1-1) preferably has a melting point of 360°C or less and a glass transition temperature of 150°C or more. From the viewpoint of heat resistance, the melting point of the polyimide resin is more preferably 280°C or more, and further preferably 290°C or more. From the viewpoint of high molding processability, it is preferably 345°C or less, more preferably 340°C or less, and further preferably 335°C or less. In addition, from the viewpoint of heat resistance, the glass transition temperature of the polyimide resin (a1-1) is more preferably 160°C or more, and further preferably 170°C or more. From the viewpoint of high molding processability, it is preferably 250°C or less, more preferably 230°C or less, and further preferably 200°C or less.
[0139] The melting point and glass transition temperature of the polyimide resin (a1-1) can be measured using a differential scanning calorimeter.
[0140] In addition, for the polyimide resin (a1-1), from the viewpoint of improving crystallinity, heat resistance, mechanical strength, and chemical resistance, the heat of the crystallization exothermic peak observed when the polyimide resin is melted and cooled at a temperature drop rate of 20°C / min (hereinafter also referred to as "crystallization exothermic heat") measured by a differential scanning calorimeter is preferably 5.0 mJ / mg or more, more preferably 10.0 mJ / mg or more, and further preferably 17.0 mJ / mg or more. The upper limit of the crystallization exothermic heat is not particularly limited, but is usually 45.0 mJ / mg or less.
[0141] The melting point, glass transition temperature and crystallization heat of the polyimide resin (a1-1) can be specifically measured by the methods described in Examples.
[0142] The logarithmic viscosity of a 0.5 mass % concentrated sulfuric acid solution of the polyimide resin (a1-1) at 30°C is preferably in the range of 0.2 to 2.0 dL / g, more preferably in the range of 0.3 to 1.8 dL / g. If the logarithmic viscosity is above 0.2 dL / g, sufficient mechanical strength can be obtained when the obtained polyimide resin composition is made into a molded body, and if it is below 2.0 dL / g, molding processability and operability become good. The logarithmic viscosity μ is obtained by measuring the flow time of concentrated sulfuric acid and the above-mentioned polyimide resin solution at 30°C using a Cannon-Fenske viscometer and based on the following formula.
[0143] μ=ln(t s / t0) / C
[0144] t0: Flow time of concentrated sulfuric acid
[0145] t s : Flow time of polyimide resin solution
[0146] C: 0.5 (g / dL)
[0147] The weight average molecular weight Mw of the polyimide resin (a1-1) is preferably 10,000 to 150,000, more preferably 15,000 to 100,000, further preferably 20,000 to 80,000, further preferably 30,000 to 70,000, further preferably 35,000 to 65,000. When the weight average molecular weight Mw of the polyimide resin (a1-1) is 10,000 or more, the mechanical strength of the obtained molded body becomes good, when it is 40,000 or more, the stability of the mechanical strength becomes good, and when it is 150,000 or less, the thermoformability becomes good.
[0148] The weight average molecular weight Mw of the polyimide resin (a1-1) can be measured by a gel permeation chromatography (GPC) method using polymethyl methacrylate (PMMA) as a standard sample.
[0149] (Method for producing polyimide resin (a1-1))
[0150] The polyimide resin (a1-1) can be produced by reacting a tetracarboxylic acid component containing a tetracarboxylic acid having at least one aromatic ring and / or a derivative thereof with a diamine component containing a diamine having at least one alicyclic hydrocarbon structure and a chain aliphatic diamine.
[0151] For the tetracarboxylic acid containing at least one aromatic ring, it is preferably a compound in which four carboxyl groups are directly bonded to the aromatic ring, and an alkyl group may also be included in the structure. In addition, the aforementioned tetracarboxylic acid is preferably a tetracarboxylic acid having 6 to 26 carbon atoms. As the aforementioned tetracarboxylic acid, pyromellitic acid, 2,3,5,6-toluenetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, etc. are preferred. Among these, pyromellitic acid is more preferred.
[0152] As the derivative of tetracarboxylic acid containing at least one aromatic ring, there can be mentioned: anhydride or alkyl ester of tetracarboxylic acid containing at least one aromatic ring. The above-mentioned tetracarboxylic acid derivative is preferably a tetracarboxylic acid derivative having 6 to 38 carbon atoms. As the anhydride of tetracarboxylic acid, there can be mentioned: pyromellitic acid monoanhydride, pyromellitic acid dianhydride, 2,3,5,6-toluenetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, etc. Examples of the alkyl esters of tetracarboxylic acids include dimethyl pyromellitic acid, diethyl pyromellitic acid, dipropyl pyromellitic acid, diisopropyl pyromellitic acid, dimethyl 2,3,5,6-toluenetetracarboxylate, dimethyl 3,3',4,4'-diphenylsulfonetetracarboxylate, dimethyl 3,3',4,4'-benzophenonetetracarboxylate, dimethyl 3,3',4,4'-biphenyltetracarboxylate, and dimethyl 1,4,5,8-naphthalenetetracarboxylate. In the alkyl esters of the tetracarboxylic acids, the number of carbon atoms in the alkyl group is preferably 1 to 3.
[0153] As the tetracarboxylic acid and / or its derivative containing at least one aromatic ring, at least one compound selected from the above may be used alone or in combination of two or more compounds.
[0154] The carbon number of the diamine containing at least one alicyclic hydrocarbon structure is preferably 6 to 22, and examples thereof include 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,2-cyclohexanediamine, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, 4,4'-diaminodicyclohexylmethane, 4,4'-methylenebis(2-methylcyclohexylamine), carvonediamine, limonenediamine, isophoronediamine, norbornanediamine, bis(aminomethyl)tricyclo[5.2.1.0 2,6 ] decane, 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 4,4'-diaminodicyclohexylpropane, etc. These compounds can be used alone or in combination of two or more compounds selected from these. Among these, 1,3-bis(aminomethyl)cyclohexane is preferably used. It should be noted that the diamine containing an alicyclic hydrocarbon structure usually has structural isomers, but the ratio of cis-isomer / trans-isomer is not limited.
[0155] The chain aliphatic diamine may be straight chain or branched, and the number of carbon atoms is preferably 5 to 16, more preferably 6 to 14, and further preferably 7 to 12. In addition, if the number of carbon atoms in the chain portion is 5 to 16, an ether bond may be contained in the middle thereof. Preferred chain aliphatic diamines include, for example, 1,5-pentamethylenediamine, 2-methylpentane-1,5-diamine, 3-methylpentane-1,5-diamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undemethylenediamine, 1,12-dodecamethylenediamine, 1,13-tridecamethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine, and 2,2'-(ethylenedioxy)bis(ethyleneamine).
[0156] The chain aliphatic diamine may be used alone or in combination of two or more. Among these, chain aliphatic diamines having 8 to 10 carbon atoms are preferably used, and at least one selected from the group consisting of 1,8-octamethylenediamine and 1,10-decamethylenediamine is particularly preferably used.
[0157] When the polyimide resin (a1-1) is produced, the molar ratio of the amount of the diamine containing at least one alicyclic hydrocarbon structure to the total amount of the diamine containing at least one alicyclic hydrocarbon structure and the chain aliphatic diamine is preferably 20 to 70 mol%. The molar ratio is preferably 25 mol% or more, more preferably 30 mol% or more, and further preferably 32 mol% or more. From the viewpoint of expressing high crystallinity, it is preferably 60 mol% or less, more preferably 50 mol% or less, further preferably less than 40 mol%, and further preferably 35 mol% or less.
[0158] The diamine component may contain a diamine containing at least one aromatic ring. The diamine containing at least one aromatic ring preferably has 6 to 22 carbon atoms, and examples thereof include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,2-diethynylphenylenediamine, 1,3-diethynylphenylenediamine, 1,4-diethynylphenylenediamine, 1,2-diaminobenzene, 1,3-diaminobenzene, 1,4-diaminobenzene, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, α,α'-bis(3-aminophenyl)-1,4-diisopropylbenzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,6-diaminonaphthalene, and 1,5-diaminonaphthalene.
[0159] In the above, the molar ratio of the amount of the diamine containing at least one aromatic ring to the total amount of the diamine containing at least one alicyclic hydrocarbon structure and the chain aliphatic diamine is preferably 25 mol% or less. On the other hand, the lower limit is not particularly limited and may be greater than 0 mol%.
[0160] From the viewpoint of improving heat resistance, the molar ratio is preferably 5 mol% or more, more preferably 10 mol% or more, and from the viewpoint of maintaining crystallinity, it is preferably 20 mol% or less, more preferably 15 mol% or less.
[0161] From the viewpoint of reducing coloration of the polyimide resin, the molar ratio is preferably 12 mol% or less, more preferably 10 mol% or less, further preferably 5 mol% or less, and further preferably 0 mol%.
[0162] When producing the polyimide resin (a1-1), the charging amount ratio of the tetracarboxylic acid component and the diamine component is preferably 0.9 to 1.1 mol of the diamine component per 1 mol of the tetracarboxylic acid component.
[0163] In addition, when manufacturing the polyimide resin (a1-1), in addition to the aforementioned tetracarboxylic acid component and the aforementioned diamine component, an end-capping agent may also be mixed. As the end-capping agent, at least one selected from the group consisting of monoamines and dicarboxylic acids is preferred. The amount of the end-capping agent used is an amount that can introduce a desired amount of terminal groups into the polyimide resin (a1-1), preferably 0.0001 to 0.1 mol, more preferably 0.001 to 0.06 mol, and further preferably 0.002 to 0.035 mol relative to 1 mol of the aforementioned tetracarboxylic acid and / or its derivative.
[0164] Among them, as the end-capping agent, a monoamine end-capping agent is preferred. From the viewpoint of introducing the aforementioned chain aliphatic group having 5 to 14 carbon atoms at the end of the polyimide resin (a1-1) to improve the heat aging resistance, a monoamine having a chain aliphatic group having 5 to 14 carbon atoms is more preferred, and a monoamine having a saturated straight-chain aliphatic group having 5 to 14 carbon atoms is further preferred.
[0165] The blocking agent is particularly preferably at least one selected from the group consisting of n-octylamine, isooctylamine, 2-ethylhexylamine, n-nonylamine, isononylamine, n-decylamine and isodecylamine; further preferably at least one selected from the group consisting of n-octylamine, isooctylamine, 2-ethylhexylamine, n-nonylamine and isononylamine; most preferably at least one selected from the group consisting of n-octylamine, isooctylamine and 2-ethylhexylamine.
[0166] As a polymerization method for producing the polyimide resin (a1-1), a known polymerization method can be adopted, and the method described in International Publication No. 2016 / 147996 can be used.
[0167] From the viewpoint of improving the machinability and micromachinability of the obtained molded body, the viewpoint of the ease of thermoforming, and the viewpoint of obtaining low dielectric properties, the content of the polyimide resin (a1-1) in the component (A) is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and is 100% by mass or less.
[0168] From the viewpoint of thermoformability and the viewpoint of improving the machinability and micromachinability of the obtained molded body, the content of component (A) in the thermoplastic resin composition is preferably 40% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, further preferably 65% by mass or more, further preferably 70% by mass or more. From the viewpoint of improving the machinability and micromachinability of the obtained molded body, it is preferably 95% by mass or less, more preferably 90% by mass or less, further preferably 85% by mass or less, further preferably 80% by mass or less.
[0169] <Component (B): Inorganic filler containing zirconium oxide (b1)>
[0170] The thermoplastic resin composition of the present invention contains an inorganic filler containing zirconium oxide (b1) as a component (B).
[0171] By using the thermoplastic resin (A) and the inorganic filler (B) containing a predetermined amount of zirconium oxide (b1), a molded body having excellent machinability and fine processing properties can be produced.
[0172] (Component (b1): zirconium oxide)
[0173] The shape of the zirconium oxide (b1) used in the present invention is not particularly limited, and examples thereof include spherical, plate-like, flaky, columnar, and fibrous shapes. Among these, spherical or plate-like particles are preferred, and spherical particles are more preferred, from the viewpoint of improving the machinability and micromachinability of the resulting molded body.
[0174] From the viewpoint of improving the machinability and micromachinability of the obtained molded body, and from the viewpoint of availability, zirconium oxide (b1) preferably has a small particle size. For example, from the viewpoint of improving the machinability and micromachinability of the obtained molded body, the volume median particle size (D50) of component (b1) is preferably 1 μm or less, more preferably 0.80 μm or less, further preferably 0.60 μm or less, further preferably 0.50 μm or less, and further preferably 0.40 μm or less. In addition, from the viewpoint of improving the machinability and micromachinability of the obtained molded body, availability, and improving operability, it is usually 0.01 μm or more, more preferably 0.02 μm or more, and further preferably 0.05 μm or more.
[0175] D50 of the component (b1) can be measured using a laser diffraction light scattering particle size distribution analyzer.
[0176] Examples of commercially available zirconium oxide particles used as component (b1) include KZ series manufactured by Kyoritsu Materials Co., Ltd., TZ series manufactured by Tosoh Corporation, and UEP series manufactured by Daiichi Kizenso Kagaku Kogyo Co., Ltd. Among them, KZ series high-purity zirconium oxide "KZ-0Y-LSF" manufactured by Kyoritsu Materials Co., Ltd. can be appropriately selected.
[0177] From the viewpoint of improving the machinability and micromachinability of the obtained molded body, the content of component (b1) in component (B) is preferably 20 mass % or more, more preferably 30 mass % or more, further preferably 35 mass % or more, further preferably 40 mass % or more, further preferably 50 mass % or more, further preferably 60 mass % or more, and is 100 mass % or less, preferably 90 mass % or less, more preferably 80 mass % or less, further preferably 70 mass % or less.
[0178] From the viewpoint of thermoformability and the viewpoint of improving the machinability and micromachinability of the obtained molded body, the content of the component (b1) is 2 to 40 parts by mass, preferably 5 to 35 parts by mass, more preferably 5 to 30 parts by mass, further preferably 10 to 30 parts by mass, and further preferably 20 to 30 parts by mass, based on 100 parts by mass of the component (A) in the thermoplastic resin composition.
[0179] (Component (b2): Inorganic filler other than component (b1))
[0180] The component (B) may be an inorganic filler composed only of the component (b1), or may further contain an inorganic filler (b2) other than the component (b1).
[0181] Component (b2) includes talc, mica, silica, alumina, wollastonite, silicon nitride, aluminum nitride, boron nitride, silicon carbide, boron carbide, calcium carbonate, titanium oxide, zinc oxide, calcium oxide, magnesium carbonate, barium carbonate, magnesium sulfate, barium sulfate, antimony trisulfide, tin sulfide, copper sulfide, iron sulfide, bismuth sulfide, zinc sulfide, etc., and one or more of these can be used.
[0182] Among the above, from the viewpoint of improving the machinability and fine processing of the obtained molded body, as component (b2), it is preferred to be at least one selected from the group consisting of talc, mica, silica, alumina, silicon nitride, aluminum nitride, boron nitride, silicon carbide, boron carbide, calcium carbonate and titanium oxide; more preferably at least one selected from the group consisting of talc, mica, silica and titanium oxide; further preferably at least one selected from the group consisting of talc and silica; and further preferably talc. It should be noted that, in the case of wishing to further improve the low dielectric properties, hollow inorganic fillers such as hollow silica and hollow alumina are preferably used.
[0183] The shape of component (b2) is not particularly limited, and examples thereof include spherical, plate-like, flaky, columnar, and fibrous shapes. Among these, spherical or plate-like particles are preferred from the perspective of improving the machinability and micromachinability of the resulting molded body and the perspective of availability.
[0184] From the viewpoint of improving the machinability and micromachinability of the obtained molded body, and the viewpoint of availability, the volume median particle size (D50) of component (b2) is preferably 3 μm or less, more preferably 2 μm or less, further preferably 1.5 μm or less, further preferably 1.2 μm or less, and further preferably 1 μm or less. In addition, from the viewpoint of improving the machinability and micromachinability of the obtained molded body, availability, and the viewpoint of improving operability, it is usually 0.01 μm or more, more preferably 0.05 μm or more, and further preferably 0.1 μm or more.
[0185] D50 of the component (b2) can be measured by the same method as that of the component (b1).
[0186] When component (b2) is used, from the viewpoint of thermoformability and improving the machinability and micromachinability of the obtained molded body, the content of component (b2) in component (B) is preferably 80 mass % or less, more preferably 70 mass % or less, further preferably 65 mass % or less, further preferably 60 mass % or less, further preferably 50 mass % or less, further preferably 40 mass % or less, and is preferably 1 mass % or more, more preferably 5 mass % or more, further preferably 10 mass % or more, further preferably 15 mass % or more, further preferably 20 mass % or more, further preferably 30 mass % or more.
[0187] When the component (b2) is used, the content of the component (b2) is preferably 1 to 40 parts by mass, more preferably 2 to 30 parts by mass, further preferably 5 to 30 parts by mass, and further preferably 10 to 20 parts by mass, relative to 100 parts by mass of the component (A) in the thermoplastic resin composition, from the viewpoint of improving the machinability and fine processing properties of the obtained molded body.
[0188] From the viewpoint of thermoformability and the viewpoint of improving the machinability and micromachinability of the obtained molded body, the content of the component (B) is 2 to 60 parts by mass, preferably 5 to 50 parts by mass, more preferably 10 to 45 parts by mass, further preferably 15 to 45 parts by mass, further preferably 20 to 45 parts by mass, further preferably 25 to 45 parts by mass, further preferably 30 to 45 parts by mass, based on 100 parts by mass of the component (A) in the thermoplastic resin composition.
[0189] <Additives>
[0190] The thermoplastic resin composition of the present invention may contain additives other than component (B) such as reinforcing fibers, matting agents, plasticizers, antistatic agents, anti-coloring agents, anti-gelling agents, colorants, slip improvers, antioxidants, conductive agents, and resin modifiers as necessary. In particular, by using graphite, carbon black, graphite, Ketjen black, or carbon nanotubes as antistatic agents, sufficient antistatic effects can be exhibited even when added in a small amount that does not impair the properties of the thermoplastic resin composition of the present invention, and they can be suitably used.
[0191] When the above-mentioned additives are used, the blending amount thereof is not particularly limited, but is generally 50% by mass or less, preferably 0.0001 to 30% by mass, more preferably 0.001 to 15% by mass, and further preferably 0.01 to 10% by mass in the thermoplastic resin composition from the viewpoint of expressing the effect of the additive.
[0192] In addition, the thermoplastic resin composition of the present invention may contain other resins other than the thermoplastic resin (A) within a range that does not hinder the properties thereof. When the thermoplastic resin (A) is used in combination with other resins other than the thermoplastic resin (A), the mixing ratio is not particularly limited as long as it is within a range that does not hinder the properties of the thermoplastic resin composition.
[0193] However, from the viewpoint of obtaining the effects of the present invention, the total content of the component (A) and the component (B) in the thermoplastic resin composition of the present invention is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 90% by mass or more, and is 100% by mass or less.
[0194] The thermoplastic resin composition of the present invention may be in any form, but is preferably in the form of pellets.
[0195] The thermoplastic resin composition of the present invention can be granulated, for example, by the following method: adding thermoplastic resin (A), inorganic filler (B) and various optional components as needed and dry blending, or feeding inorganic filler (B) and optional components separately from the position where the thermoplastic resin (A) is fed to the extruder, then, melt-kneading is carried out in the extruder and the strand is extruded, and the strand is cut to granulate. In addition, by introducing the pellets into various molding machines and performing thermoforming according to the method described later, it is possible to easily manufacture a molded body with a desired shape. On the other hand, a molded body can also be obtained without pellet form. For example, a thermoplastic resin (A), an inorganic filler (B) and various optional components as needed are added and dry blended, then a blended material is put into a mold, and compression molding is performed by hot pressing, then a molded body can also be directly obtained.
[0196] From the viewpoint of forming a pellet form and performing compression molding, the thermoplastic resin composition of the present invention preferably does not contain a solvent. Specifically, the content of the solvent in the thermoplastic resin composition is preferably 5% by mass or less, more preferably 1% by mass or less, and further preferably 0.1% by mass or less.
[0197] [Molding body]
[0198] The present invention provides a molded article comprising the above-mentioned thermoplastic resin composition.
[0199] The molded body of the present invention can be manufactured by thermoforming the aforementioned thermoplastic resin composition. As the thermoforming method, injection molding, extrusion molding, inflation molding, blow molding, hot press molding (compression molding), vacuum molding, pressure molding, laser molding, welding, welding, etc. can be mentioned. As long as it is a molding method via a hot melting process, it can be molded by any method. From the viewpoint of thermoforming using the aforementioned pellets and cutting the obtained molded body, injection molding or extrusion molding is preferred. In particular, injection molding is preferred from the viewpoint of production efficiency, and extrusion molding is preferred from the viewpoint of higher dimensional stability.
[0200] The method for producing the molded article varies depending on the melting point or glass transition temperature of the thermoplastic resin (A). When the thermoplastic resin (A) contains the polyimide resin (a1-1), it is preferred to have a step of thermoforming the thermoplastic resin composition at 290 to 380° C. Thermoforming may be performed at a temperature exceeding 380° C. to 400° C., but from the viewpoint of suppressing the degradation of the thermoplastic resin (A) and other components, thermoforming is preferably performed at a temperature of 380° C. or less. As a specific procedure, for example, the following method can be cited.
[0201] First, an inorganic filler (B) and various optional components as required are added to a thermoplastic resin (A) and dry-mixed, and then introduced into an extruder, preferably melted at 290 to 380° C., melt-kneaded and extruded in an extruder to prepare pellets. Alternatively, a thermoplastic resin (A) may be introduced into an extruder, preferably melted at 290 to 380° C., an inorganic filler (B) and various optional components as required are introduced therein, melt-kneaded and extruded with the thermoplastic resin (A) in an extruder, thereby preparing the pellets.
[0202] After the pellets are dried, they are introduced into various molding machines and thermoformed preferably at 290 to 380° C., thereby producing a molded body having a desired shape.
[0203] The molded body obtained by the above-mentioned thermoforming may be further subjected to cutting or the like to obtain a desired shape. For example, an injection molded body may be produced using the above-mentioned thermoplastic resin composition, and then subjected to cutting to obtain a molded body having a desired shape.
[0204] From the viewpoint of further improving the machinability and fine machinability, the molded body obtained by the above-mentioned thermoforming is preferably further annealed. For the molded body obtained by further annealing after thermoforming the thermoplastic resin composition, when cutting is performed, a flat plate with low surface roughness and less warping on the cut surface can be obtained. In addition, the flat plate can be used to form finer through holes.
[0205] The annealing temperature can be set according to the type of thermoplastic resin (A) used. When the thermoplastic resin (A) is a crystalline thermoplastic resin (a1), the annealing temperature is a temperature lower than the melting point of the crystalline thermoplastic resin (a1) from the viewpoint of avoiding deformation of the molded body. From the viewpoint of further improving machinability and fine processing and avoiding deformation of the molded body, when the melting point of the crystalline thermoplastic resin (a1) is set to Tm (°C), it is preferably in the range of Tm-100°C to Tm-20°C. When the thermoplastic resin (A) is an amorphous thermoplastic resin (a2), from the viewpoint of avoiding deformation of the molded body, the annealing treatment temperature is a temperature lower than the glass transition temperature of the amorphous thermoplastic resin (a2). From the viewpoint of further improving machinability and fine processing properties and avoiding deformation of the molded body, when the glass transition temperature of the amorphous thermoplastic resin (a2) is set to Tg (°C), it is preferably in the range of Tg-100°C to Tg-20°C.
[0206] Regarding specific examples of the annealing treatment temperature, when the thermoplastic resin (A) contains the aforementioned polyimide resin (a1-1), from the viewpoint of further improving machinability and fine processing properties, and from the viewpoint of avoiding deformation of the molded body, the annealing treatment temperature is preferably in the range of 200 to 360°C, more preferably 220 to 340°C, further preferably 240 to 330°C, and further preferably 250 to 320°C.
[0207] The annealing treatment time is not particularly limited, but is preferably in the range of 1 to 120 minutes, more preferably 5 to 60 minutes, from the viewpoint of further improving the machinability and micromachinability of the molded body and improving the production efficiency.
[0208] The annealing treatment of the formed body can be performed using a known heating device.
[0209] After the annealing treatment, it is preferred to perform slow cooling until the temperature reaches 100° C. or lower from the viewpoint of suppressing warping of the molded body due to residual stress.
[0210] [Components of IC socket for inspection]
[0211] The present invention also provides a component of an IC socket for inspection (hereinafter also simply referred to as "the component of the present invention" or "component") obtained by processing the above-mentioned molded body.
[0212] Examples of the inspection IC socket in this specification include an IC socket for product inspection (test socket), an IC socket for burn-in test (burn-in socket), and the like.
[0213] The member of the present invention may be a member constituting at least a part of an IC socket for inspection, and may be, for example, a substantially flat member used in a location where a device to be inspected is mounted. The substantially flat member has a fine through hole for embedding the device.
[0214] The component of the present invention can be produced, for example, by the following method. First, the thermoplastic resin composition is used to perform thermoforming (preferably injection molding) to produce a molded body. Then, preferably after annealing, the molded body is cut using an electric drill or the like to obtain a cut plate. The cut plate is finely processed using an electric drill, laser, or the like to form a plurality of through holes, thereby obtaining a component having a desired shape.
[0215] Figure 1 It is a schematic plan view showing one embodiment of a component 100 of the IC socket for inspection. Figure 1 In the figure, 10 is a cut plate, and 20 is a through hole forming region.
[0216] From the viewpoint of improving fine processing properties, the machined surface of the machined plate 10 used to produce the component 100 preferably has a low surface roughness. For example, the arithmetic mean roughness (Ra) of the machined surface of the machined plate 10 is preferably 1 μm or less, more preferably 0.8 μm or less, further preferably 0.6 μm or less, and further preferably 0.3 μm or less.
[0217] Specifically, the arithmetic mean roughness can be measured by the method described in Examples.
[0218] In the through hole forming area 20, a plurality of through holes are regularly arranged at narrow intervals. Usually, the aperture of the through hole is selected in the range of Φ0.01 to 0.20 mm and the interval is selected in the range of 0.02 to 0.40 mm. It should be noted that when the aperture is 0.1 mm or more, various probes such as wire probes and spring probes can be used, which is suitable. When the aperture is less than 0.1 mm, a wire probe with a smaller diameter can be used to adapt to more delicate inspections, which is suitable.
[0219] When the molded body produced by injection molding using the thermoplastic resin composition of the present invention is subjected to cutting, the surface roughness of the cutting surface is low, and the cutting processability becomes good. In addition, when a plurality of through holes are opened at a narrow pitch on the obtained cutting plate by using an electric drill, laser, etc., the pore size distribution is not easily increased, the pattern collapses, and the burrs are not easily generated, and the microprocessability is also good.
[0220] In addition, the molded product produced by injection molding using the thermoplastic resin composition of the present invention has excellent machinability as described above, and therefore has excellent adaptability to applications requiring precision machining such as gears, bearings, and watch cases in addition to IC socket components.
[0221] Example
[0222] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto. In addition, various measurements and evaluations in each of the production examples and Examples were performed as follows.
[0223] <Infrared spectroscopy analysis (IR measurement)>
[0224] The IR measurement of the polyimide resin was performed using “JIR-WINSPEC50” manufactured by JEOL Ltd.
[0225] <Logarithmic viscosity μ>
[0226] The polyimide resin was dried at 190 to 200° C. for 2 hours, and then 0.100 g of the polyimide resin was dissolved in 20 mL of concentrated sulfuric acid (96%, manufactured by Kanto Chemical Co., Ltd.), and the obtained polyimide resin solution was used as a measurement sample and measured using a Cannon-Fenske viscometer at 30° C. The logarithmic viscosity μ was determined based on the following formula.
[0227] μ=ln(t s / t0) / C
[0228] t0: Flow time of concentrated sulfuric acid
[0229] t s : Flow time of polyimide resin solution
[0230] C: 0.5 g / dL
[0231] <Melting point, glass transition temperature, crystallization temperature, crystallization heat>
[0232] The melting point Tm, glass transition temperature Tg, crystallization temperature Tc, and crystallization heat ΔHm of the polyimide resin were measured using a differential scanning calorimeter (“DSC-6220” manufactured by SII Technology Co., Ltd.).
[0233] The polyimide resin was subjected to the following thermal history under a nitrogen atmosphere: the first heating (heating rate 10°C / min), followed by cooling (temperature drop rate 20°C / min), and then the second heating (heating rate 10°C / min).
[0234] The peak top value of the endothermic peak observed during the second temperature increase is read to determine the melting point Tm. The value observed during the second temperature increase is read to determine the glass transition temperature Tg. The peak top value of the exothermic peak observed during cooling is read to determine the crystallization temperature Tc.
[0235] In addition, the crystallization heat generation amount ΔHm (mJ / mg) was calculated based on the area of the exothermic peak observed during cooling.
[0236] <Half crystallization time>
[0237] The half crystallization time of the polyimide resin is measured using a differential scanning calorimeter ("DSC-6220" manufactured by SII Technology Co., Ltd.).
[0238] The measurement conditions of the polyimide resin with a half-crystallization time of less than 20 seconds are as follows: in a nitrogen environment, keep it at 420°C for 10 minutes to completely melt the polyimide resin, and then perform a rapid cooling operation at a cooling rate of 70°C / minute. At this time, the time taken from the appearance of the observed crystallization peak to the peak top is calculated to determine it.
[0239] <Weight average molecular weight>
[0240] The weight average molecular weight (Mw) of the polyimide resin was measured under the following conditions using a gel permeation chromatography (GPC) measuring apparatus "Shodex GPC-101" manufactured by Showa Denko K.K.
[0241] Column: Shodex HFIP-806M
[0242] Mobile phase solvent: HFIP containing 2 mM sodium trifluoroacetate
[0243] Column temperature: 40°C
[0244] Mobile phase flow rate: 1.0 mL / min
[0245] Sample concentration: about 0.1 mass%
[0246] Detector: IR detector
[0247] Injection volume: 100μm
[0248] Standard curve: Standard PMMA
[0249] Production Example 1 (Production of Polyimide Resin 1)
[0250] Into a 2L separable flask equipped with a Dean-Stark apparatus, a Liebig condenser, a thermocouple, and four stirring blades, 500 g of 2-(2-methoxyethoxy)ethanol (manufactured by Nippon Emulsifier Co., Ltd.) and 218.12 g (1.00 mol) of pyromellitic dianhydride (manufactured by Mitsubishi Gas Chemical Co., Ltd.) were introduced, nitrogen gas was introduced, and then stirred at 150 rpm until a uniform suspension solution was formed. On the other hand, using a 500 mL beaker, 49.79 g (0.35 mol) of 1,3-bis(aminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., cis / trans ratio = 7 / 3) and 93.77 g (0.65 mol) of 1,8-octamethylenediamine (manufactured by Kanto Chemical Co., Ltd.) were dissolved in 250 g of 2-(2-methoxyethoxy)ethanol to prepare a mixed diamine solution. The mixed diamine solution was slowly added using a plunger pump. The dropwise addition caused heat generation, and the internal temperature was adjusted to be controlled at 40 to 80°C. During the dropwise addition of the mixed diamine solution, nitrogen was allowed to flow and the stirring blade speed was set to 250 rpm. After the dropwise addition was completed, 130 g of 2-(2-methoxyethoxy)ethanol and 1.284 g (0.0100 mol) of n-octylamine (manufactured by Kanto Chemical Co., Ltd.) as a capping agent were added, and further stirred. At this stage, a light yellow polyamic acid solution is obtained. Next, the stirring speed is set to 200 rpm, and then the polyamic acid solution in the 2L separable flask is heated to 190°C. During the heating process, it is confirmed that the liquid temperature is between 120 and 140°C with the precipitation of polyimide resin powder and the dehydration accompanied by imidization. After keeping at 190°C for 30 minutes, it is placed to cool to room temperature and filtered. The obtained polyimide resin powder is washed and filtered using 300g of 2-(2-methoxyethoxy)ethanol and 300g of methanol, and then dried at 180°C for 10 hours using a dryer to obtain 317g of powder of polyimide resin 1 as a crystalline thermoplastic resin.
[0251] The IR spectrum of polyimide resin 1 was measured. The results showed that ν(C=O) was 1768, 1697 (cm- 1 ) The characteristic absorption of the imide ring was observed at . The logarithmic viscosity was 1.30 dL / g, Tm was 323°C, Tg was 184°C, Tc was 266°C, the crystallization heat was 21.0 mJ / mg, the half crystallization time was less than 20 seconds, and the Mw was 55,000.
[0252] The composition and evaluation results of the polyimide resin of Production Example 1 are shown in Table 1. In addition, the mol % of the tetracarboxylic acid component and the diamine component in Table 1 are values calculated based on the input amount of each component when producing the polyimide resin.
[0253] [Table 1]
[0254] Table 1
[0255]
[0256] *1: Content ratio (mol %) of the repeating structural unit of formula (1) relative to the sum of the repeating structural unit of formula (1) and the repeating structural unit of formula (2) in the polyimide resin 1
[0257] The abbreviations in Table 1 are as follows.
[0258] PMDA; Pyromellitic Dianhydride
[0259] 1,3-BAC; 1,3-bis(aminomethyl)cyclohexane
[0260] OMDA; 1,8-octamethylenediamine
[0261] Examples 1 to 9 and Comparative Examples 1 to 6 (Production and Evaluation of Thermoplastic Resin Compositions and Molded Articles (1))
[0262] The components (A) and (B) shown in Table 2 were fully mixed by dry blending. The obtained mixed powder was extruded into strands with a diameter of 2 to 3 mm using a co-rotating twin-screw kneading extruder ("HK-25D-41D" manufactured by PARKER CORPORATION, screw diameter: 25 mm) at a barrel temperature of 360°C and a screw speed of 120 rpm. The extrusion amount and extrudability of the strands at this time were observed, and the manufacturing stability of the resin composition during twin-screw extrusion was evaluated according to the following criteria.
[0263] <Manufacturing stability during twin-screw extrusion>
[0264] The extrusion rate (kg / h) and extrudability of the strands extruded from the twin-screw kneading extruder in the above-described manner were observed, and the production stability of the resin composition during twin-screw extrusion was evaluated according to the following criteria.
[0265] AA: Extrusion rate exceeds 4kg / h, and the strands are extruded evenly.
[0266] A: The extrusion rate is 3-4kg / h, and the strands are extruded evenly.
[0267] B: The extrusion rate is 3-4 kg / h, and the extrusion strands are uneven.
[0268] C: Extrusion volume is less than 3kg / h.
[0269] The strands extruded from the extruder were air-cooled and then pelletized using a pelletizer ("Fan-cutter FC-Mini-4 / N" manufactured by Hoshi Plastic Co., Ltd.). The obtained pellets (thermoplastic resin composition) were dried at 150°C for 10 hours and then used for injection molding.
[0270] Injection molding was performed using an injection molding machine ("ROBOSHOTα-S30iA" manufactured by FANUC Corporation) at a barrel temperature of 375°C, a mold temperature of 200°C, and a molding cycle of 60 seconds to produce a flat plate-shaped injection molded body of 70 mm×70 mm×4 mm in thickness. The injection moldability at this time was evaluated by the following method.
[0271] <Injection moldability evaluation>
[0272] The injection moldability of the resin composition was evaluated based on the following three items.
[0273] (Device load)
[0274] The resin composition pelletized in the above method was fed into the cylinder of the above injection molding machine, and the torque at this time was observed. The load on the device was evaluated according to the following criteria.
[0275] A: When pellets are fed into the barrel, there is enough margin until the torque limit.
[0276] B: When the pellets are fed into the barrel, they can be formed although they are near the torque limit.
[0277] C: When the pellets are fed into the barrel, the torque limit is reached and it is difficult to form.
[0278] (Surface roughness of molded body)
[0279] The surface of the injection-molded article obtained in the above-described manner was visually observed, and the surface roughness was evaluated according to the following criteria.
[0280] AA: No silver streaks or bubbles were generated.
[0281] A: Only a few silver streaks or bubbles appear.
[0282] B: A large number of silver streaks or bubbles are produced, but they are not spread all over the surface.
[0283] C: A large number of silver streaks or bubbles were observed on the entire surface.
[0284] (Scorch of the molded body)
[0285] The surface of the injection molded product obtained by continuously performing injection molding 10 times in the above method was visually observed, and scorch was evaluated according to the following criteria.
[0286] AA: No scorching was observed during 10 consecutive injection moldings.
[0287] A: Scorching was gradually observed during 10 consecutive injection moldings.
[0288] B: Scorching was observed from the first injection molding.
[0289] C: Scorching was observed from the first injection molding, and the scorching gradually intensified.
[0290] <Machinability Evaluation (1)>
[0291] The machinability of the injection-molded article was evaluated according to the following method.
[0292] (Surface roughness during cutting)
[0293] The injection molded body obtained by the above method was cut to produce a flat plate with a thickness of 50 mm×50 mm×3 mm. The arithmetic mean roughness (Ra) of a continuous range of 20 mm in length along a direction perpendicular to the cutting direction was measured on the cut surface of the obtained flat plate using a 3D shape measuring device ("VR-6000" manufactured by Keyence Corporation), and the surface roughness was evaluated according to the following criteria.
[0294] A: Arithmetic mean roughness is less than 0.6 μm
[0295] B: Arithmetic mean roughness is more than 0.6 μm and less than 1 μm
[0296] C: Arithmetic mean roughness exceeds 1μm
[0297] <Evaluation of micromachinability (1)>
[0298] The micromachinability of the flat plate (cutting plate) was evaluated based on the following two items.
[0299] (Pore size distribution of micropores (100 μm))
[0300] exist Figure 1 In the region 20 (within an area of about 3 mm×3 mm) near the center of the aforementioned 50 mm×50 mm×3 mm thick cut plate 10, 24×24 through holes (a total of 576 through holes) were drilled at a pitch of 0.12 mm using an electric drill (drill diameter: Φ0.10 mm). The diameters of the through holes formed were measured using a high-precision image dimensioning device (LM series manufactured by Keyence Corporation), and the distribution of the diameters was evaluated according to the following criteria.
[0301] A: The diameter of the through holes falls between Φ0.090 and 0.110 mm.
[0302] C: The diameter of the through hole may be outside the range of Φ0.090 to 0.110 mm.
[0303] (Appearance of micropores (100μm) and burr status)
[0304] The appearance of the through-hole formed by the above method was observed with a digital microscope ("VHX-7000" manufactured by Keyence Corporation, magnification: 50 times) and evaluated according to the following criteria.
[0305] AA: No pattern collapse and few burrs.
[0306] A: There is a little pattern collapse and rough edges.
[0307] C: There is a large pattern collapse, holes are close to each other, or there are a lot of burrs.
[0308] The above evaluation results are shown in Table 2. Note that, since Comparative Examples 2 and 5 had poor injection moldability, the machinability and micromachinability after injection molding could not be evaluated.
[0309] [Table 2]
[0310]
[0311] Examples 6, 10 to 12 (Production and Evaluation of Thermoplastic Resin Composition and Molded Article (2))
[0312] The components (A) and (B) shown in Table 3 were fully mixed by dry blending. The obtained mixed powder was extruded into strands with a diameter of 2 to 3 mm using a co-rotating twin-screw kneading extruder ("HK-25D-41D" manufactured by PARKER CORPORATION, screw diameter: 25 mm) at a barrel temperature of 360°C and a screw speed of 120 rpm.
[0313] The strands extruded from the extruder were air-cooled and then pelletized using a pelletizer ("Fan-cutter FC-Mini-4 / N" manufactured by Hoshi Plastic Co., Ltd.). The obtained pellets (thermoplastic resin composition) were dried at 150°C for 10 hours and then used for injection molding.
[0314] An injection molding machine ("ROBOSHOTα-S30iA" manufactured by FANUC (Co., Ltd.)) was used to perform injection molding under the conditions of a barrel temperature of 375°C, a mold temperature of 200°C, and a molding cycle of 60 seconds to produce a flat plate-shaped injection molded body having a thickness of 70 mm×70 mm×4 mm. The injection molded body was annealed for 60 minutes at the temperature described in Table 3 using an air supply constant temperature thermostat ("DN610H" manufactured by Yamato Scientific (Co., Ltd.) and slowly cooled to room temperature, the injection molded body was recovered, and then evaluated according to the following method.
[0315] <Machinability Evaluation (2)>
[0316] The machinability of the injection molded body after the annealing treatment was evaluated based on the following two items.
[0317] (Warping during cutting)
[0318] The injection molded article obtained in the above method was cut to produce a flat plate of 50 mm×50 mm×3 mm in thickness. The warping state of the obtained flat plate was confirmed from 8 directions using a strain gauge and evaluated according to the following criteria.
[0319] A: Warpage in all eight directions is 40 μm or less.
[0320] B: Warpage exceeding 40 μm was found at one or more locations.
[0321] C: The whole surface has large fluctuations and the warpage is difficult to measure.
[0322] (Surface roughness during cutting)
[0323] The injection molded body obtained by the above method was cut to produce a flat plate with a thickness of 50 mm×50 mm×3 mm. The arithmetic mean roughness (Ra) of a continuous range of 20 mm in length along a direction perpendicular to the cutting direction was measured on the cut surface of the obtained flat plate using a 3D shape measuring device ("VR-6000" manufactured by Keyence Corporation), and the surface roughness was evaluated according to the following criteria.
[0324] AA: Arithmetic average roughness is less than 0.3μm
[0325] A: Arithmetic mean roughness is more than 0.3 μm and less than 0.6 μm
[0326] B: Arithmetic mean roughness is more than 0.6 μm and less than 1 μm
[0327] C: Arithmetic mean roughness exceeds 1μm
[0328] <Evaluation of micromachinability (2)>
[0329] The micromachinability of the flat plate (cutting plate) was evaluated based on the following two items.
[0330] (Pore size distribution of micropores (50 μm))
[0331] exist Figure 1 In the region 20 (within an area of about 3 mm×3 mm) near the center of the aforementioned 50 mm×50 mm×3 mm thick cut plate 10, 4×20 through holes (a total of 80 through holes) were drilled at a pitch of 0.1 mm using an electric drill (drill diameter: Φ0.05 mm). The diameters of the through holes formed were measured using a high-precision image dimensioning device (LM series manufactured by Keyence Corporation), and the distribution of the diameters was evaluated according to the following criteria.
[0332] A: The diameter of the through holes falls between Φ0.047 and 0.053 mm.
[0333] C: The diameter of the through hole may be outside the range of Φ0.047 to 0.053 mm.
[0334] It should be noted that in Table 3, the cases where micro-machining itself is difficult to perform are marked as "-".
[0335] (Appearance of micropores (50μm) and burr status)
[0336] The appearance of the through-hole formed by the above method was observed with a digital microscope ("VHX-7000" manufactured by Keyence Corporation, magnification: 50 times) and evaluated according to the following criteria.
[0337] AA: No pattern collapse and few burrs.
[0338] A: There is a little pattern collapse and rough edges.
[0339] C: There is a large pattern collapse, holes are close to each other, or there are a lot of burrs.
[0340] It should be noted that in Table 3, the cases where micro-machining itself is difficult to perform are marked as "-".
[0341] The above evaluation results are shown in Table 3. As can be seen from Table 3, the molded bodies of Examples 10 to 12 subjected to annealing treatment are more excellent in machinability and micromachinability than the molded body of Example 6 which is not subjected to annealing treatment.
[0342] [Table 3]
[0343] Table 3
[0344]
[0345] The details of each component shown in Table 2 and Table 3 are as follows.
[0346] <Thermoplastic resin (A)>
[0347] (a1-1) Polyimide resin 1 obtained in Production Example 1
[0348] <Inorganic filler (B)>
[0349] (b1) Zirconia, high-purity zirconium oxide "KZ-0Y-LSF" manufactured by Kyoritsu Materials Co., Ltd., spherical particles, D50: 0.2 μm, Mohs hardness: 8
[0350] (b2-1) Silica, "KS-1" manufactured by Kyoritsu Materials Co., Ltd., plate-shaped particles, D50: 1.4 μm, Mohs hardness: 7
[0351] (b2-2) Talc, "NanoACE D-800" manufactured by Nippon Talc Co., Ltd., plate-shaped particles, D50: 0.8 μm, Mohs hardness: 1
[0352] (b2-3) Mica, hard mica "A-11" made by YAMAGUCHI MICA, plate-like particles, D50: 3 μm, Mohs hardness: 2.0 to 3.2
[0353] Industrial Applicability
[0354] According to the thermoplastic resin composition of the present invention, a molded body having excellent machinability and micromachinability can be produced. The molded body is suitable for producing a component of an IC socket for inspection, etc.
[0355] Description of Reference Numerals
[0356] 100: Inspection components of IC socket
[0357] 10: Cutting plate
[0358] 20: Through hole formation area
Claims
1. A thermoplastic resin composition comprising component A and component B, Component A: at least one thermoplastic resin selected from the group consisting of a crystalline thermoplastic resin a1 having a melting point of 270° C. or higher and an amorphous thermoplastic resin a2 having a glass transition temperature of 200° C. or higher, Component B: an inorganic filler material containing zirconium oxide b1, The content of the component b1 is 2 to 40 parts by mass relative to 100 parts by mass of the component A. The content of the component B is 2 to 60 parts by mass relative to 100 parts by mass of the component A.
2. The thermoplastic resin composition according to claim 1, wherein The component A is at least one selected from the group consisting of polyimide resins, polyetherimide resins, polyetherimide sulfone resins, polyphenylene sulfide resins, polyetheretherketone resins, polyetherketoneketone resins, liquid crystal polymers, and wholly aromatic polyester resins other than liquid crystal polymers.
3. The thermoplastic resin composition according to claim 1 or 2, wherein The component A comprises a polyimide resin a1-1, wherein the polyimide resin a1-1 comprises a repeating structural unit represented by the following formula (1) and a repeating structural unit represented by the following formula (2), and the content ratio of the repeating structural unit of the formula (1) is 20 to 70 mol% relative to the total of the repeating structural unit of the formula (1) and the repeating structural unit of the formula (2). R1 is a divalent group having 6 to 22 carbon atoms and containing at least one alicyclic hydrocarbon structure, R2 is a divalent chain aliphatic group having 5 to 16 carbon atoms, and X1 and X2 are each independently a tetravalent group having 6 to 22 carbon atoms and containing at least one aromatic ring.
4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein The volume median particle size (D50) of the component b1 is 1 μm or less.
5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein The component b1 is in the form of spherical particles.
6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein The component B further includes an inorganic filler b2 other than the component b1, and the component b2 is at least one selected from the group consisting of talc, mica, silica, alumina, silicon nitride, aluminum nitride, boron nitride, silicon carbide, boron carbide, calcium carbonate, and titanium oxide.
7. The thermoplastic resin composition according to claim 6, wherein The content of the component b2 is 1 to 40 parts by mass relative to 100 parts by mass of the component A. 8 . A molded product comprising the thermoplastic resin composition according to claim 1 .
9. A component of an IC socket for inspection, which is obtained by processing the molded article according to claim 8.
Citation Information
Patent Citations
Low-contaminated injection-molded form
JP2005290328A
Test sockets, test socket manufacturing methods, and test socket jig assemblies
JP2018529932A
Flame-retardant polyimide shaping material and shaped body
WO2021024624A1